Playful teaching and learning - Walsh, Glenda; McMillan, Dorothy; McGuinness, Carol (SAGE, 2017)
"Every early years practitioner should be able to captivate and maintain the interest of young children in their setting, through the provision of a playful learning experience. Covering age ranges 3-8 years, Playful Teaching and Learning explores the importance of infusing playfulness throughout the entire early years day, and includes chapters that: - Establish the core principles underpinning playful teaching and learning - Help students and practitioners understand how playfulness can be applied to all aspects of the early years curriculum including mathematics, literacy, outdoor environments, science & technology, and ICT - Explore core issues in early years provision including observing, planning & assessment, and how they relate to playful learning - Emphasize the role and qualities of the playful professional. This is a fantastic resource for any student or practitioner looking to enrich the lives of young children through meaningful playful learning experiences. "--Back cover.